GANGGUAN KESEHATAN KERJA DAN KECELAKAAN PADA PETUGAS UNIT REKAM MEDIS DI BAGIAN FILING RUMAH SAKIT ROEMANI MUHAMMADIYAH SEMARANG TAHUN 2019 - Dita Anggita Sari; Fitria Wulandari (Dian Nuswantoro Semarang, 2020)
The officer has the potential to fall while taking documents and experience respiratory problems due to the amount of dust. The purpose of this study was to determine the risk of health problems and workplace accidents that can occur in the medical records filing unit officer Roemani Muhammadiyah Hospital Semarang uses descriptive research type. Research methods by interview and observation. The research subjects were 2 filing officers and the object of research was the filing room From the results of the research conducted obtained lighting 56.8 lux filing space. filing room with an area of 4.80 X 16 m2, 1 AC with 1.5 PK, temperature around 23.9 ° C. Expose a little dust. Officers rarely use masks and almost never wear gloves. Health disorders which include low risk: eye pain, low back pain, shortness of breath, back pain, fatigue, dizzy, overheating, falling / slipping. Moderate risks include: Aches, Tingling, slashed documents and high risks include: Coughing colds, sneezing, sneezing, falling over objects / documents are not organized To reduce the risk factors for workplace accidents and increase staff knowledge on Occupational Health Safety it is recommended to provide a brochure containing the importance of Occupational Health Safety Keywords: Medical Record, Health Problems, Occupational Health Safety